STUDIES ON THE CURRENT SITUATION OF PROJECTS UNSELECTED FOR FINANCING, IN THE MEAT PROCESSING SECTOR, THROUGH THE NATIONAL RURAL DEVELOPMENT PROGRAM IN ROMANIA - Daniel Valeriu ULIU; Liviu OLARU; Marius VLADU2 (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Through the National Rural Development Program (NRDP), applicants have the opportunity to create or develop a business, with public support of up to 100% of the project value, depending on the type of investment and beneficiary. The projects submitted online on the Agency for Financing Rural Investments (AFRI) website will be selected based on the “Regulation on the organization and functioning (ROF) of the process of selection and verification of appeals for projects related to the measures of the National Rural Development Program (NRDP) 2014–2020. The application for funding will be declared eligible without funding, ineligible or withdrawn by the beneficiary. The purpose of this study is to analyze the situation of submitted and unfunded projects through sub-measure 4.2 of NRDP 2014-2020, in the analysis period 2015-2019, in the field of meat processing. An analysis will be made from the point of view of the number of unfunded projects, their eligible value and their public value, and in order to have an overview, the connection between the consulting companies and the number of unfunded projects in this field will be obvious. In the period 2015-2019, 96 projects in the field of meat processing were submitted and unfunded, in which 73 were eligible without funding, 15 ineligible and 8 withdrawn projects, with a total eligible value of 76,060,938 euros (public value 40,558,548). From the correlations between the number of consulting firms and the number of unfunded projects, it results that the projects were submitted randomly, independently of the consulting firms from each county of the respective regions.